DEVELOPMENT OF VIRTUAL REALITY-BASED MULTIMEDIA MODELING AND SIMULATION LEARNING TO ACHIEVE MEANINGFUL LEARNING - KARMILA SURYANI; KHAIRUDIN KHAIRUDIN; RINI WIDYASTUTI; MEIRIANI ARMEN; ADE FITRI RAHMADANI; RAHMA DINA POHAN (SOSIOEDUKASI, 2026)
This research aims to develop Virtual Reality (VR)-based learning multimedia for the Modeling and Simulation course as an effort to achieve meaningful learning in higher education. The study employed a Research and Development (R&D) method consisting of several stages, including needs analysis, design, validation, and product testing. Data analysis was conducted through the validity test of the practicality questionnaire, expert validation of the media, and practicality testing by users. The validity test of the instrument involving 63 respondents showed that all items were valid at a 5% significance level. Expert validation results indicated an average validity score of 91%, categorized as highly valid, covering aspects of material content, visual communication, user design, and software utilization. The practicality test conducted with 63 students of the Informatics and Computer Education Study Program revealed that the VR-based learning multimedia was highly practical, easy to use, and effective in enhancing students’ understanding of Modeling and Simulation concepts. The interface design dominated by blue tones provided a calm and comfortable learning atmosphere. Based on these findings, it can be concluded that the Virtual Reality-based learning multimedia developed in this study is highly valid and practical, and therefore suitable for broader implementation as an innovative learning medium to enhance the quality and meaningfulness of students’ learning experiences.